Biolubrication Synthesis Made from Used Cooking Oil and Bayah Natural Zeolite Catalyst - Agus Rochmat; Athia Hasna Nurhanifah; Yunita Parviana; Suaedah Suaedah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Automotive growth in Indonesia continues to increase, thus the needed of material that supported such as lubricants have also increased. To support environment to have a sustainable development, the world needs biodegradable lubricant or biolubricant. Biolubricant can match the characteristics and replace the function of petroleum-based lubricants. The biolubricant base material at the moment was the vegetable oil through a series of physically and chemically modified. This research synthesizes used cooking oil into biolubricant using natural zeolite catalyst, which in its production included esterification process of used cooking oil, synthesis of methyl ester and biolubricant synthesis. Biolubicant synthesis was conducted by variation of methyl ester mole ratio with ethylene glycol of 1:13-40 and catalyst mass range of 0.5%-3%. The results of the study showed that the highest yield was 83.46%, density 0.8994 g/mL, viscosity 40°C 52.90 cSt and at 100°C 8.74 cSt, the pour point 6°C and the flash point 278°C.